The Strategic Role Of Visionary Leadership In Islamic Educational Institutions In The Vuca Era - Elvi Rahmi; Rike Ifriadi; Susi Ratna Sari (Jurnal Pendidikan Vokasi Indonesia, 2025)
Rapid and unpredictable changes have positioned education within the VUCA era, characterized by volatility, uncertainty, complexity, and ambiguity. Islamic educational institutions are required to adapt to these changes while maintaining Islamic values and educational objectives. In this situation, leadership becomes a crucial factor in determining institutional resilience and competitiveness. This study aims to examine the role of visionary leadership in strengthening Islamic educational institutions in the VUCA era. This research uses a qualitative library research method by analyzing scientific journals, books, and relevant academic literature as the primary data sources. The study focuses on exploring the concept of visionary leadership and its implementation in Islamic educational institutions facing rapid social, technological, and educational transformation. The findings indicate that visionary leadership plays a strategic role in encouraging institutional adaptability and innovation. Visionary leaders are able to integrate Islamic values with digital transformation, promote technology-based learning, and strengthen organizational culture through collaboration and continuous improvement. In addition, visionary leadership contributes to the development of human resources by enhancing teacher professionalism, creativity, and collective commitment toward institutional goals. The study also reveals that Islamic educational institutions led by visionary leaders tend to be more responsive to educational disruption, more capable of maintaining institutional identity amid globalization, and more effective in creating sustainable educational innovation. Therefore, visionary leadership can be considered a transformative leadership model that is highly relevant for Islamic educational institutions in addressing the challenges of the VUCA era.